Impact of Montelukast on Allergic Rhinitis and Asthma as Emerging New Treatment Option - Muhammad Ali Lal Bux, Talha Laique (Pakistan Journal of Medical & Health Sciences, 2024)
Background: AR (allergic rhinitis) is a condition that causes chronic nasal mucosal inflammation. Among the regional signs of AR are sneezing, rhinorrhea, nasal discomfort, and nasal congestion. AR places a considerable financial and social impact on both the person with AR and society. There is mounting evidence that AR may elevate inflammatory mediators throughout the body and raise the chance of developing asthma. Aim: To determine the degree to which Montelukast altered the symptoms and signs of allergic rhinitis (AR) and asthma, as well as to estimate the proportion of participants who were adversely affected. The absolute eosinophil count and five essential asthma and allergic rhinitis symptoms were assessed before and after therapy. Method: This was a randomized trial. This experiment at the Lahore General Hospital involved 204 participants with asthma and allergic rhinitis. Participants received either (budesonide) BD (256 mg) with (montelukast) MNT (10mg) + MNT for two weeks, or BD alone (256 mg). The data was entered and analysed in SPSS 23. Results:However, when compared to BD alone, BD + MNT demonstrated noticeably greater improvements in nasal blockage and itching. Both treatments greatly lessened the five primary symptoms as compared to the baseline. After two weeks of treatment, absolute eosinophil counts in BD + MNT significantly surpassed BD. Practical Implication: Asthma and allergic rhinitis are major problems nowadays. This investigation will help find better answers to this problem. BD+ MNT is a more successful treatment for this illness. Conclusion:BD + MNT therapy may be more efficient overall than BD monotherapy for those with asthma and allergic rhinitis, especially in lowering nasal obstruction, itching, and subclinical lower airway inflammation. The absolute eosinophil count can also be used to monitor a patient’s response to treatment for allergic rhinitis. Keywords: Asthama, budesonide, montelukast, and allergic rhinitis. Key words: Montelukast, allergic rhinitis, Asthma, Emerging New Treatment Option